851Predictors and causes of inappropriate shocks by subcutaneous defibrillators (S-ICD) in a cohort of sardinian Brugada syndrome patients. (18th June 2020) - Berne, P M; Fancello, T; Viola, G; Carboni, V; Mula, G; Ortu, S; Lorenzoni, G; Merella, P; Motta, G; Casu, G
Abstract: Funding Acknowledgements: Project Code CRP- 6175. Regione Autonoma della Sardegna Background: The subcutaneous defibrillator (S-ICD) is an attractive option for patients with Brugada syndrome (BrS) at high risk, as it is highly effective to prevent arrhythmic sudden cardiac death (SCD) while avoiding some of the complications associated to transvenous devices. However, S-ICD are not free from complications, one of the most common being inappropriate shocks. Objective: To assess the causes and predictors of inappropriate shocks by subcutaneous defibrillators (S-ICD) in a cohort of sardinian BrS patients Methods: From February 2013 to September 2019, 373 patients were diagnosed as BrS patients. Sixty-five patients were considered to be at high risk of SCD, and implanted with an ICD. Of them, 36 were implanted with an S-ICD. Patients went through regular follow-up visits (physical examination, 12-lead ECG, device interrogation, occurrence of symptoms). Appropriate and inappropriate shocks were analyzed to establish their cause. Results: Thirty-six BrS patients were implanted with an S-ICD (9.7% of the total BrS group, 55% of ICD implants). Twenty-four patients (67%) were male, mean age at diagnosis was 45± 14 y.o., and 31 (86%) were probands.  Seventeen patients (47%) had a family history of SCD. Ten patients (28%) had a spontaneous type 1 ECG at diagnosis and 14 (19%) had an spontaneous type 1 ECG at least once since the diagnosis, 2 patients (5.7%) had a type 1 ECG during fever, and 11 (31%) presented an S wave ≥40 msec in lead DI. Twelve patients (33%) underwent EP study, and 8 (67%) were inducible for ventricular fibrillation. During a mean follow-up of 46 ± 67 months, 2 patients (6%) had appropriate shocks, while 5 (14%) had inappropriate shocks. The rate between inappropriate and appropriate shock was 2.5.  The causes of inappropriate shock were T-wave oversensing (4 patients, 80%) and air entrapment (1 patient, 20%). Gender, proband status, sport practice, family history of SCD, type 1 ECG during fever, S wave ≥40 msec in lead DI, VF inducibility EP study, or the presence of symptoms during the follow-up (vaso-vagal syncope, arrhythmic syncope, nocturnal enuresis, ventricular fibrillation, atrial fibrillation) did not associated with inappropriate shock; neither did the technique of screening for S-ICD (manual or automated tool) nor the selected vector of sensing of the S-ICD. A spontaneous type 1 ECG at diagnosis (4 (80%) versus 6 (21%), p = 0.009), or at any time from diagnosis during follow-up (4 (80%) versus 10 (33%), p = 0.0049) and having a high-pass filter programmed OFF/not available [3 (75% versus 7 (25%), p = 0.044], were significantly associated with inappropriate shock of S-ICD in these population. Conclusions: Brugada syndrome patients implanted with S-ICD present a higher rate of inappropriate shock compared to appropriate shock (2.5 times). Patients with spontaneous type 1 ECG are at  higher risk to receive inappropriate shock from S-ICDs, while programming a high-pass filter ON may prevent some of these episodes.